Gestational Diabetes Mellitus An Overview with Some Recent Advances - Ray, Amita (IntechOpen, 2020)
This book on gestational diabetes does not claim to cover all aspects of this complex and ever-evolving medical condition. It is an attempt by the group of authors to provide an overview, highlight important features, and bring to light certain recent advances in the diagnosis, screening, and understanding of gestational diabetes mellitus. As the book provides an overview of the condition, we are sure that reading it would provide medical undergraduates and postgraduates a quick revision for their exams. The current concepts section of the book may inspire more exploration into this area.It has been a pleasure to work with experts, both senior and junior, for this endeavor but we are particularly grateful to the publisher IntechOpen who have shown commitment and perseverance in completing this work. This new book deserves to be a success and we are sure it will be.